Serafina and the twisted staff - Beatty, Robert (Egmont, 2016)
Once hidden in the dusty basement of the Biltmore Estate where her pa worked as hired help, young Serafina now struggles to adjust to her new life of airs and graces upstairs in the grand house. Uncertain about what the discovery of her mother in the dark forests that surround the house means, Serafina finds herself caught between two very different lives. But when a sinister arrival threatens her whole world, Serafina and her new friend Braeden must solve the mystery of this new evil before it engulfs everything - and everyone - they've ever known ...